Observations on Lutsi oral tradition - Salve, Kristi (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2021)
This article examines Lutsi intangible culture in an attempt to clarify the origins of this language island. Historical stories about coming from “Sweden” refer to southern Estonia, but such stories are also widespread in areas that were never under Swedish rule. The Christian tradition is based on the church language and literature of Estonia. Lutsi laments or lament-like songs are unique, different from Seto laments, but also from the lament-like orphan songs of southern Estonia. Work songs and ritual songs (tavandilaul) as well as narrative songs are related to traditions found in both Võromaa and Setomaa. Oskar Kallas’s documentation contains an impressive number of children’s songs and readings, short verses, and other peripheral material. Their proportion only increases in later collections. The influence of Latvian songs is striking and can be seen from direct translations to texts where original and borrowed material intermingle. The Lutsi tradition was also probably influenced by their Slavic neighbours. Comparisons with the folklore of the other South Estonian language islands and that of the Tver Karelians shows both commonalities and differences. Kokkuvõte. Kristi Salve: Tähelepanekuid Lutsi maarahva suulisest pärimusest. Artiklis on vaadeldud Lutsi maarahva vaimset kultuuri, püüdes selgust tuua keelesaare kujunemisloosse. Ajaloolised jutud „Rootsi“ päritolust viitavad küll Lõuna-Eestile, kuid sellised jutud on levinud ka aladel, mis pole Rootsi võimu alla kuulunudki. Lutsi kristlik pärimus lähtub Eesti kirikukeelest ja -kirjandusest. Lutsi itkud või itkulaadsed laulud on omapärased, erinedes setu itkudest, aga ka Lõuna-Eesti itkulaadsetest vaeslapselauludest. Töö- ja tavandilaulud, samuti jutustavad laulud seostuvad nii Võrumaa kui ka Setumaa traditsiooniga. Juba Oskar Kallase kogus on silmapaistvalt palju lastele mõeldud laule ja lugemisi, lühikesi (pilke)salmikesi ja muud perifeerset rahvaluule ainest. Hilisemates kogudes nende osakaal suureneb. Silmapaistev on läti laulude ...